Rab10-associated tubulation as an early marker for biogenesis of the assembly compartment in cytomegalovirus-infected cells - Mahmutefendić Lučin, Hana; Štimac, Igor; Marcelić, Marina; Skočaj, Matej; Lisnić, Berislav; Omerović, Alen; Viduka, Ivona; Radić, Barbara; Karleuša, Ljerka; Blagojević Zagorac, Gordana; Deželjin, Martina; Jurak Begonja, Antonija; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCytomegalovirus (CMV) infection reorganizes early endosomes (EE), recycling endosome (RE), and trans-Golgi network (TGN) and expands their intermediates into a large perinuclear structure that forms the inner part of the cytoplasmic assembly complex (AC). The reorganization begins and results with the basic configuration (known as pre-AC) in the early (E) phase of infection, but the sequence of developmental steps is not yet well understood. One of the first signs of the establishment of the inner pre-AC, which can be observed by immunofluorescence, is the accumulation of Rab10. This study aims to investigate whether Rab10-positive domain (Rab10-PD) is expanded during the E phase of infection.MethodsWe performed long-term live imaging of EGFP-Rab10 with epifluorescence imaging-enhanced digital holotomographic microscopy (DHTM), confocal imaging of known Rab10 interactors and identification of important Rab10 interactors with the proximity-dependent biotin identification assay (BioID). The accumulation of Rab10-PD was analyzed after knock-down of EHBP1 and Rabin8, two proteins that facilitate Rab10 recruitment to membranes, and after blocking of PI(4,5)P2 by PI(4,5)P2-binding protein domains.ResultsOur study shows the gradual expansion of Rab10-PD in the inner pre-AC, the association of Rab10 with EHBP1 and MICAL-L1, and the dependence of Rab10-PD expansion on EHBP1 and PI(4,5)P2 but not Rabin8, indicating the expansion of EE-derived tubular recycling endosome-like membranes in the pre-AC. Silencing of Rab10 and EHBP1 suggests that Rab10-PD expansion is not required for the establishment of the inner pre-AC nor for the expansion of downstream tubular domains.ConclusionThe present work characterizes one of the earliest sequences in the establishment of pre-AC and suggests that subsets of EE-derived tubular membranes may serve as the earliest biomarkers in pre-AC biogenesis. Our study also indicates that the pre-AC biogenesis is complex and likely involves multiple parallel processes, of which Rab10-PD expansion is one. Our experiments, particularly our silencing experiments, show that Rab10 and EHBP-1 do not play a significant role in the later stages of inner pre-AC biogenesis or in the expansion of downstream tubular domains. A more comprehensive understanding of the tubular domain expansion remains to be established.